In-silico DFT studies and molecular docking evaluation of benzimidazo methoxy quinoline-2-one ligand and its Co, Ni, Cu and Zn complexes as potential inhibitors of Bcl-2, Caspase-3, EGFR, mTOR, and PI3K, cancer-causing proteins - K Kaavin; D Naresh; MR Yogeshkumar; M Krishna Prakash; S Janarthanan; M Murali Krishnan; M Malathi (Chemical Physics Impact, 2024)
We present here the design, Density Functional Theory (DFT) and Molecular Docking studies of Benzimidazo Methoxy Quinoline-2-one (BMQ) ligand-coordinated transition metal complexes (Co, Ni, Cu, and Zn). Two types of metal coordination, namely imidazole-metal (Im-metal) and quinoline-metal (Q-metal), are proposed in the metal coordination process. The observed lower negative values of both metal coordination on molecular optimization, confirmed structural stability of metal complexes compared with BMQ ligand. An average energy difference of -18.7152 eV lower energy of Im-metal complexes with reference to Q-metal complexes illustrated the more coordination capability of imidazole-imine functionality. Molecular stability and reactivity of the proposed complexes have been assessed through frontier molecular orbital (FMO), and molecular electrostatic potential (MEP) map studies. The molecular descriptor values, calculated from the FMO studies, elucidate the higher probability and strong protein binding affinity for the Im-metal complexes. To predict their antiproliferative properties, BMQ-transition metal complexes are computationally analyzed with proteins Bcl-2, Caspase-3, EGFR, mTOR, and PI3K. Based on these results, four active metal complexes are selected and subjected to in-silico ADMET profiling to evaluate their pharmacological potential. From all the findings, a new mechanism for molecular design aimed at target-oriented protein binding is concluded